1985
DOI: 10.1002/food.19850290705
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sulphur‐organic compounds obtained by thermal treatment of the meat broths in the presence of alkyl‐mercaptopropanol

Abstract: By means of GLC-analysis on columns with different polarity phases the composition of the sulphur-containing volatiles obtained by the thermal treatment of the industrial broths and alkyl-mercaptopropanol was studied using flame-photometric detector specific for sulphur. The identification of the sulphur-containing compounds was realized using both retention indices and GLC-MS. The comparison of the composition of sulphur-containing flavour components of the industrial broth with that of its product with alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…28,29 Compound 3 was identified in simulated meat flavors 30 and thermal treatment of the meat broths in the presence of alkyl-mercaptopropanol. 31 To date, the aroma properties of compounds 2 and 3 have not been well studied.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Compound 3 was identified in simulated meat flavors 30 and thermal treatment of the meat broths in the presence of alkyl-mercaptopropanol. 31 To date, the aroma properties of compounds 2 and 3 have not been well studied.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…AGE contains enantiomers of both 2 and 3 at a ratio of about 50:50. Yu et al reported that compound 2 was tentatively identified in baked blanched garlic, fried blanched garlic, and thermally degraded alliin. , Compound 3 was identified in simulated meat flavors and thermal treatment of the meat broths in the presence of alkyl-mercaptopropanol . To date, the aroma properties of compounds 2 and 3 have not been well studied.…”
Section: Resultsmentioning
confidence: 99%
“…For 3-(alkylthio)-1-propanethiols ( = 3), characteristic peaks with m/e 107 and 106 corresponding to [M -(R)]"+ and [M -(R-(-H))]*+, respectively. Such fragments are not generated from molecular ions of all other n-(alkylthio)-1 -alkanethiols.n-(Alkylthio) -1-alkanethiols 1 have been identified as flavors in natural compounds and foodstuffs Golovnya et al, 1983;Mikhailova et al, 1975;Schutte and Koenders, 1972) and have been proposed as warning agents for gaseous hydrocarbon fuels (Crouch and Williams, 1974). It has been shown that they are generated by thermal treatment of industrial broths (Mikhailova et al, 1975); e.g., they have been detected in the headspace of simmering beef broth (Brinkman et al., 1972a;Schutte et al, 1972).…”
mentioning
confidence: 99%
“…Such fragments are not generated from molecular ions of all other n-(alkylthio)-1 -alkanethiols.n-(Alkylthio) -1-alkanethiols 1 have been identified as flavors in natural compounds and foodstuffs Golovnya et al, 1983;Mikhailova et al, 1975;Schutte and Koenders, 1972) and have been proposed as warning agents for gaseous hydrocarbon fuels (Crouch and Williams, 1974). It has been shown that they are generated by thermal treatment of industrial broths (Mikhailova et al, 1975); e.g., they have been detected in the headspace of simmering beef broth (Brinkman et al., 1972a;Schutte et al, 1972). They have also been found in the aroma of synthetic meat flavors obtained by baker's yeast autolysate in Maillard reactions (Golovnya et al., 1983), and it has been discovered that such com-…”
mentioning
confidence: 99%
See 1 more Smart Citation